OMA orthology in 2021: website overhaul, conserved isoforms, ancestral gene order and more. Issue Volume 49:Issue D1(2021) (11th November 2020) - Altenhoff, Adrian M; Train, Clément-Marie; Gilbert, Kimberly J; Mediratta, Ishita; Mendes de Farias, Tarcisio; Moi, David; Nevers, Yannis; Radoykova, Hale-Seda; Rossier, Victor; Warwick Vesztrocy, Alex; Glover, Natasha M; Dessimoz, Christophe
Abstract: OMA is an established resource to elucidate evolutionary relationships among genes from currently 2326 genomes covering all domains of life. OMA provides pairwise and groupwise orthologs, functional annotations, local and global gene order conservation (synteny) information, among many other functions. This update paper describes the reorganisation of the database into gene-, group- and genome-centric pages. Other new and improved features are detailed, such as reporting of the evolutionarily best conserved isoforms of alternatively spliced genes, the inferred local order of ancestral genes, phylogenetic profiling, better cross-references, fast genome mapping, semantic data sharing via RDF, as well as a special coronavirus OMA with 119 viruses from the Nidovirales order, including SARS-CoV-2, the agent of the COVID-19 pandemic. We conclude with improvements to the documentation of the resource through primers, tutorials and short videos. OMA is accessible at https://omabrowser.org .